620.92 DEVELOPMENT AND IMPROVEMENT OF DRYING TECHNOLOGIES IN A SOLAR DRYER: Solar dryer - Muxtarov, Dilmurod (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
It was found that in the first 4 hours of the solar installation, the residual mass dries up to 67%, 38%, 17%, and 13%. In direct sunlight, it has been determined to dry up to 75%, 43%, 18%, and 12%. These results substantiated the ability of the solar dryer to ensure an efficient drying process compared to traditional open solar drying methods. In the second stage of the experiment, products of the same mass were placed in 3 mm for each layer. As a result, it was found that in the first 3 hours, the residual mass on the 1st and 2nd floors was dried equally to 77%, 61%, and 47%, and on the 3rd floor - to 75%, 57%, and 44%. This indicates that the possibility of drying products on the 3rd floor is uneven compared to the 1st and 2nd floors. In the third stage of the experiment, a carrot product with a thickness of 3 mm, 5 mm, 8 mm, and 10 mm was dried during one sunny day. As a result, the possibility of drying products with a thickness of 3 mm during any sunny day of the drying season was determined.